2011
DOI: 10.1021/np2002918
|View full text |Cite
|
Sign up to set email alerts
|

Biologically Active Arborinane-Type Triterpenoids and Anthraquinones from Rubia yunnanensis

Abstract: Twelve new arborinane-type triterpenoids (1-12) and four new anthraquinones (13-16), together with 50 known compounds, were isolated from the roots of Rubia yunnanensis. The structures of 1-16 were elucidated by spectroscopic data analysis and chemical methods. All compounds were evaluated for their cytotoxic, antibacterial, and antifungal activities. Rubiyunnanol C (5) is the first example of an arborinane-type triterpenoid with a double bond at C-8-C-9.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 30 publications
2
51
0
Order By: Relevance
“…The NMR data indicated that 1 was a phenylpropanoid, which was very similar with those of 3 [8]. In comparison with 3, the only difference is a hexanoyl (δ C 173.8 (C-1"), 34.3 (C-2"), 24.7 (C-3"), 31.4 (C-4"), 22.4 (C-5"), 14.0 (C-6")) in 1 replaced the isovaleryl (δ C 173.0 (C-1"), 43.4 (C-2"), 25.7 (C-3"), 22.4 (C-4", 5")) in 3. The 1 H-1 H COSY correlations ( Figure 1) between H-2" and H-3", H-3" and H-4", H-4" and H-5", H-5" and H-6", and the HMBC cross-peaks of H-2" with C-1" confirmed the presence of the hexanoyl in 1.…”
Section: Identification Of New Compoundsmentioning
confidence: 60%
See 4 more Smart Citations
“…The NMR data indicated that 1 was a phenylpropanoid, which was very similar with those of 3 [8]. In comparison with 3, the only difference is a hexanoyl (δ C 173.8 (C-1"), 34.3 (C-2"), 24.7 (C-3"), 31.4 (C-4"), 22.4 (C-5"), 14.0 (C-6")) in 1 replaced the isovaleryl (δ C 173.0 (C-1"), 43.4 (C-2"), 25.7 (C-3"), 22.4 (C-4", 5")) in 3. The 1 H-1 H COSY correlations ( Figure 1) between H-2" and H-3", H-3" and H-4", H-4" and H-5", H-5" and H-6", and the HMBC cross-peaks of H-2" with C-1" confirmed the presence of the hexanoyl in 1.…”
Section: Identification Of New Compoundsmentioning
confidence: 60%
“…The NMR data of 2 was closely similar with those of 1, which suggested that 2 was also a phenylpropanoid. The only difference is that a 4"-methyl-hexanoyl (δC 174.0 (C-1"), 32.1 (C-2"), 31.4 (C-3"), 34.0 (C-4"), 29.1 (C-5"), 18.8 (C-6")) in 2 replaced the hexanoyl (δC 173.8 (C-1"), 34.3 (C-2"), 24.7 (C-3"), 31.4 (C-4"), 22.4 (C-5"), 14.0 …”
Section: Identification Of New Compoundsmentioning
confidence: 99%
See 3 more Smart Citations